APLIKASI TEORI JEROME BRUNNER DALAM MENINGKATKAN HASIL BELAJAR SISWA PADA PEMBELAJARAN GEOMETRI MATEMATIKA KELAS III SD - Evalin Ndoen (Sekolah Tinggi Pariwisata Mataram, 2022)
mathematics learning outcomes in studying geometry about the perimeter and area of flat shapes. This study is Classroom Action Research that is divided into two cycles, each with two meetings. According to Kemmis and Taggart, each cycle is implemented in stages with 32 elementary school grade III students. Observation sheets and test descriptions are used as data collection tools. The results showed that there was an increase in student learning outcomes, namely in the first cycle the average learning outcome was 70.6% which then increased in the second cycle with the percentage of learning outcomes was 86.4%. Thus, student learning outcomes in learning geometry about perimeter and area of ​​flat shapes have reached indicators of success and it can be concluded that the application of Bruner's learning theory can improve student learning outcomes on the material of circumference and area of ​​flat shapes.